The Impact of Green Human Resource Management Practices on the Sustainability of Jordan Phosphate Mines Company - Al-Ashush, Hassan Abdel Hafeez; El-Hanandeh, Rami Mohamed (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to reveal the impact of green human resource management practices on the sustainability of the Jordan Phosphate Mines Company PLC. The study followed the descriptive analytical method. A total of (350) questionnaires were distributed. (330) questionnaires valid for analysis were retrieved at a rate of (94.29%) of the total questionnaires that the researcher distributed to the study sample members working in the Jordan Phosphate Mines Company PLC. Then, the Social Statistical Package(SPSS) program was adopted for the purpose of testing hypotheses and analyzing the results.The results showed that the level of application of green human resources management practices by removing them (green employment, green training and development, and green performance evaluation) in the Jordan Phosphate Mines Company is (high). The highest factors came: green performance appraisal, followed by green recruitment and finally green training and development. The results also showed that the level of interest in achieving sustainability by its (environmental, social, economic) factors in the Jordan Phosphate Mines Company is (high). The highest factors came: the environment factor, followed by the social factor, and finally the economic factor. The results revealed an impact of the factors of green human resource management practices (green employment, green training and development, and green performance evaluation) on the factors of sustainability (environmental, social, and economic), overall degree of sustainability and with statistical significance.The study’s most prominent recommendations came about the need to pay attention to green employment by setting standards to attract workers who have positive attitudes towards green management practices, and to pay attention to green training through developing training programs in green environmental management, to increase environmental awareness and provide workers with knowledge and skills and modify their behavior towards the application of management practices. Green human resources, and attention to green performance management through the use of green performance indicators in performance evaluation and putting points in the employee evaluation form related to green practices.
Keywords: green human resource management practices; sustainability; Jordan Phosphate Mines Company PLC